Accountability and security in the cloud : First Summer School, Cloud Accountability Project, A4Cloud, Malaga, Spain, June 2-6, 2014, Revised selected papers and lectures /: First Summer School, Cloud Accountability Project, A4Cloud, Malaga, Spain, June 2-6, 2014, Revised selected papers and lectures. (2015) - Unknown
No abstract available